Jejak Jalur Rempah Nusantara dalam Catatan Sejarah Qatar: Al-Hajri, Ali Bin Ghanem. Qaṭar fī ‘Uyūn al-Rahhālah, First edition. Doha, Qatar: Hamad bin Khalifa University Press, 2020. 167 pp. ISBN: 978-9927141294. - Karyadi, Fathurrochman (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2025)
This research discusses Qatar's role in the Nusantara spice trade route using the book